Fracture behaviors of pre-cracked monolayer molybdenum disulfide: A molecular dynamics study - Xiong, Qi-lin; Li, Zhen-huan; Tian, Xiao-geng (Beilstein Journal of Nanotechnology, 2016)
The fracture strength and crack propagation of monolayer molybdenum disulfide (MoS2) sheets with various pre-existing cracks are investigated using molecular dynamics simulation (MDS). The uniaxial tensions of pre-cracked monolayer MoS2 sheets with different crack tips, different locations of crack, different crack lengths and angled cracks are simulated and studied. The results show that the configuration of crack tip can influence significantly the fracture behaviors of monolayer MoS2 sheets while the location of crack does not influence the fracture strength. With the increase of crack length, the fracture strength of monolayer MoS2 sheets reduces almost linearly, and the fracture of monolayer MoS2 sheets is transformed from almost brittle to ductile. By making comparison between the MDS results and the predictions of continuum fracture mechanics theories, including Inglis' model, Griffith's model with and without finite size effect, it is found that MDS results agree well with the predictions of Griffith's model with finite size effect, differ from the predictions of Inglis' model and Griffith's model without finite size effect. Finally, the MDS results of monolayer MoS2 sheets with different angled crack are also analyzed based on the continuum fracture mechanics model.
Keywords: crack propagation; fracture strength; molecular dynamics simulation; monolayer molybdenum disulfide; pre-existing crack